A Study on the influence of Emotionally Intelligent leaders on the work performance of the Islamic Banks in the UAE - Sembaij, Amna Saleh Ali (2011)
This dissertation aims at exploring the role of Emotional Intelligence (EI) competences in predicting job performance within the Islamic banks in the UAE. The paper is the first study in the UAE context that explorers the role of EI leaders in influencing performance effectiveness in Islamic banking. This study consists of two main concepts: Job performance and EI. A self-administrated questionnaire was developed by combining two scales. The first one was Wong and Law Emotional Intelligence Scale (2002), and the second one was Welbourne and Johnson Erez (1998) scale. The questionnaire used to survey the employees of 6 Islamic banking organisations in the United Arab Emirates. The data were collected using an online application. The factors of the two main variables (EI and Job Performance) were indentified to analyse the relationship between them. EI consists of 4 factors: Self Emotional Appraisal (SEA), other's Emotional Appraisal (OEA), Regulation of Emotions (ROE) and Use of Emotions (UOE). Job Performance consists of 5 factors: Job, Career, Innovator, Team and Organization. The correlation and regression analysis were used to test and identify the relationship between leaders EI and job performance. The results revealed a significant and positive relationship between leader’s EI and job performance of the employees of the Islamic banks. Five hypotheses linked between the EI and Job performance factors were selected to be studied in this paper and it was found that EI have a strong positive relationship with the Job performance factors. The sample consisted of only Islamic banks responses and it is limited to evaluate the EI leaders and job performance in the Islamic Banks in the UAE.